18 The State Records of the Colony of Georgia 294-95 (1759) - (:unkn) unknown (My University, 1759)
unlawful to fire "any great gun or shall arm in the town or harbour of Savannah after Sun Set without leave or permission from the Governor." Margin note says "small arm."
Keywords: DISCHARGE